In vitro assessment of antimicrobial, anti-inflammatory, and schistolarvicidal activity of macroalgae-based gold nanoparticles - Kamal, Marwa; Abdel-Raouf, Neveen; Sonbol, Hana; Abdel-Tawab, Heba; Abdelhameed, Mohamed Sayed; Hammouda, Ola; Elsayed, Khaled N. M. (Frontiers in Marine Science, 2022)
There is a growing need to improve facile, eco-friendly, and cheap approaches for nanoparticle (NP) synthesis. Green protocols have been investigated for the fabrication of NPs using several natural sources as plants, algae, fungi, and bacteria. Thus, the present study proposed a rapid, convenient, and efficient biosynthesis of gold NPs (Au-NPs) using the ethanolic extracts of three macroalgae, i.e., Cystoseira myrica, C. trinodis, and Caulerpa prolifera. The reduction of Au ions and the fabrication of Au-NPs were validated using ultraviolet-visible (UV–Vis) spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), and zeta potential analysis. The produced Au-NPs were tested for their antibacterial, antifungal, anti-inflammatory, and schistolarvicidal activity. Results revealed the formation of Au-NPs with an average size of 12.6–15.5 nm and different shapes that are mainly spherical with pure crystalline nature. The strong antibacterial activities of C. trinodis– and C. myrica–based Au-NPs against E. coli (inhibition zones of 22 and 19 mm) and against Staphylococcus aureus (inhibition zones of 18 and 20.5 and mm) were recorded, respectively. On the other hand, the high antifungal activity of C. trinodis Au-NPs against Aspergillus niger and Alternaria alternate showed the inhibition zones of 18 and 17 mm, respectively. The high antifungal activity of C. trinodis Au-NPs against Candida albicans (inhibition zone 16 mm) was also recorded. Regarding anti-inflammatory and schistolarvicidal activity, Au-NPs fabricated using C. myrica showed 64.2% of the inhibitory effect on protein denaturation and recorded the highest schistolarvicidal activity against Schistosoma mansoni cercariae that sank and died after 7 min. Overall, these findings proved that macroalgal ethanolic extracts can be effectively used for the biosynthesis of Au-NPs. These Au-NPs offer a significant alternative antimicrobial, anti-inflammatory, and schistolarvicidal agents. for biomedical uses.